"THE USE OF MODERN INNOVATIVE TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING AND ITS EFFECTIVENESS" (Conferencea, 2022)
At a time when the need for learning a foreign language is high, the effective use of modern information technologies, innovative educational technologies in the educational process makes this process more effective. The effectiveness of innovative educational technologies lies in their correct and effective use in the educational process. This article describes the use of modern innovative technologies in foreign language teaching and its effectiveness.